Are provisions and contingent liabilities priced by the market?: An exploratory study in Portugal and the UK. Issue 2 (17th April 2019) - Lopes, Ana Isabel; Reis, Laura
Abstract : Purpose: This paper aims to examine pricing differences regarding contingencies presented in statements of financial position or notes, which are considered an area for creative accounting. Design/methodology/approach: The authors have chosen two countries with different cultural environments to test the exploratory study. The sample includes companies using the International Accounting Standard (IAS) 37, which requires recognition of provisions while contingent liabilities are only disclosed, implying different impacts from underlying judgement related with contingencies. The authors apply a regression model based on the Ohlson equity-valuation framework. Findings: The most important conclusion is that market participants in both countries follow different patterns when incorporating information about provisions and contingent liabilities. More precisely, the results suggest that provisions are value-relevant, but incrementally less negative in Portugal. Contingent liabilities seem to have no value relevance. However, an exception exists for Portuguese companies having a risk committee board, in which case a significant market valuation of contingent liabilities is found and discounted in share prices. The existence of a risk committee corroborates the value relevance of this board, which is positively valued by market participants in both national cultures. Practical implications: The findings may make a contribution to the IASB research project on the IAS 37 and possible amendments to it (suspended until the revisions to the conceptual framework are finalized) and to the IASB prioritization of communication effectiveness of financial statements to all users. Originality/value: Value relevance of contingencies differentiating countries from two different national cultures and firms with a risk committee on the board of directors.